La sfida all'agricoltura tradizionale, con la tecnologia e la precisione per dare sostenibilití alle produzioni agricole moderne - Matteo Antonello (mediaGEO soc. coop., 2021)
What is precision farming and why is so important today. Considering the population growth and the everyday economical challenges, the agro industrial sector must updated the way it works introducing modern technologies to help operators, save and conserve the land and give to the end customer the best product.